Why do cocoa farmers use unapproved pesticides? Empirical evidence from Obuasi Municipality, Ghana - Wilhemina Hyde-Cooper; Prince Asiedu; Enoch Kwame Tham-Agyekum; Prince Amoako; John-Eudes Andivi Bakang; Akua Yeboah Oduro-Owusu (Cogent Social Sciences, 2024)
To address the growing demand for increased crop yields while mitigating the adverse environmental impacts of agricultural practices, a comprehensive understanding of unapproved pesticide usage among cocoa farmers in Ghana is essential. This study employed a multi-stage sampling technique and administered questionnaires for 400 cocoa farmers. Data analysis encompassed a combination of descriptive and inferential statistics. Generally, the use of unapproved pesticides among the cocoa farmers is relatively low (42%). Cocoa farmers were unsure about their reasons for using the unapproved pesticides (Mean index = 3.41). Agro-chemical shops (79%) serve as the main conduit of information for farmers’ use of unapproved pesticides. The unapproved pesticide mostly used by the farmers was ‘Gramaxone’ (16%). Significantly, the use of these unapproved pesticides was influenced by various socioeconomic factors, including education (5%), farming experience (5%), farm size (5%), access to knapsack sprayers (1%), and access to labour (1%). The study’s key takeaway is the imperative to enhance training programmes for the category of farmers who still use unapproved pesticides. By addressing this issue, it is possible to promote safer and more sustainable agricultural practices while simultaneously improving crop yields, aligning with the broader objectives of sustainable agriculture in Ghana.